Risk Factors for the Onset of Frozen Shoulder in Middle-Aged and Elderly Subjects Within 1 Year of Discharge From a Hospitalization That Involved Intravenous Infusion: A Prospective Cohort Study - Cao, Wenping; Chen, Jiangnan; Pu, Jianfeng; Fan, Yunwu; Cao, Ye (Frontiers in Medicine, 2022)
Aim: To investigate the incidence of frozen shoulder and risk factors for the onset of frozen shoulder in middle-aged and elderly subjects within 1 year of discharge from a hospitalization that involved intravenous infusion in Zhangjiagang Second People's Hospital. Methods: A total of 1,900 subjects who were discharged from a hospitalization that involved intravenous infusion in the hospital between May 2020 and September 2020 met the inclusion criteria for this study: 950 subjects had a mean daily duration of intravenous infusion ≤2 hours (low exposure) and 950 subjects had a mean daily duration of intravenous infusion ≥3 hours (high exposure). Subjects were followed up by telephone at 6 months ±1 week and 12 months ±1 week after discharge the incidence of frozen shoulder. Results: The cumulative incidence rate of frozen shoulder within 1 year of discharge was 5.2%. Multivariate logistic regression analysis revealed the risk of frozen shoulder was higher in subjects with a mean daily duration of intravenous infusion ≥3 hours compared to ≤2 hours, (OR=3.082, 95%CI 1.919-4.949, P < 0.001); subjects hospitalized for 11 to 30 days had a higher risk of frozen shoulder compared to those hospitalized for 10 days or less (OR=6.836, 95%CI 4.363-10.709, P＜0.001); subjects who were overweight/ obese (BMI ≥25 kg/m2) had a higher risk of frozen shoulder compared to those of normal weight (BMI 18.5-24.9 kg/m2) (OR =2.166, 95%CI 1.376-3.410, P=0.001); subjects in the 56- to 70-year-old age group had a higher risk of developing frozen shoulder compared to those in the 40- to 55-year-old age group (OR=1.977, 95%CI 1.154-3.387, P=0.013); diabetes increased the risk of frozen shoulder (OR=3.009, 95%CI 1.826-4.959, P<0.001). The 71-85 years old age group and hypertension were statistically significant in univariate analysis but not in multivariate analysis (P>0.05) Conclusion: The cumulative incidence rate of frozen shoulder in middle-aged and elderly subjects within 1 year of discharge from a hospitalization that involved intravenous infusion was higher. Independent risk factors for the onset of frozen shoulder included mean daily duration of intravenous infusion ≥3 hours, length of hospital stay 11-30 days, BMI ≥25 kg/m2, age 56-70 years, and diabetes.